How computers really work : a hands-on guide to the inner workings of the machine - Justice, Matthew (No Starch Press, Inc., 2021)
"A book that introduces readers to the fundamentals of hardware and software. It covers foundational aspects of computing, from binary and circuit design to the internet and modern computing, and includes a mix of exercises and hands-on activities"--